Zero products of Toeplitz operators on Reinhardt domains. Issue 1 (8th March 2022) - Čučković, Željko; Huo, Zhenghui; Şahutoğlu, Sönmez
Abstract: Let $Ω $ be a bounded Reinhardt domain in $\mathbb {C}^n$ and $φ _1, …, φ _m$ be finite sums of bounded quasi-homogeneous functions. We show that if the product of Toeplitz operators $T_{φ _m}… T_{φ _1}=0$ on the Bergman space on $Ω $, then $φ _j=0$ for some j .